Model of optical transitions in A₂B₆ wurtzite type quantum dots - Kunets, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Model of optical transitions in A₂B₆ wurtzite type quantum dots is proposed. It is based on the effective mass approximation and the quantum confinement effects, the valence band degeneracy in G point of the Brillouin zone and the effective mass anisotropy of the holes are also taken into account. A good agreement between the theoretically calculated and experimentally measured absorption spectra of CdSe and ZnxCd₁₋xS wurtzite nanocrystals embedded into a borosilicate glass matrix is achieved in the framework of the model. It is also concluded that the effective mass approximation is yet enough justified for the nanocrystals with the average radius being lowered to ~2.0 nm.